DEVELOPMENT OF SCIENTIFIC PROCESS-CREATIVE SKILLS (SP-CS) TEST ON LIGHT WAVE CONCEPT: CONTENT VALIDITY AND RASCH MODEL ANALYSIS - Royhanun Athiyyah; Selly Feranie; Taufik Ramlan Ramalis (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2022)
Most creativity assessments are carried out in general fields, whereas creativity assessments in specific fields are rarely carried out. This study aims to develop a scientific creative skills test instrument that is integrated with a scientific process skills test instrument (SP-CS test) on the light waves concept. This study used the ADDIE procedure. The research procedure consists of five stages including analyzing, designing, developing, implementing, and evaluating. The initial draft of SP-CS test consisted of 21 multiple choice scientific process skills (SPS) questions and 15 open-ended scientific creative skills (SCS) questions. The results of the expert judgement were analyzed using the content validity index (CVI) and obtained a value of 0.75 (very suitable) for the SPS instrument and 0.60 (suitable) for the SCS instrument. After being revised based on the expert suggestions, the test instrument was tested on 33 students (20 girls,13 boys) aged 17-18 years. The trial data were analyzed using the Rasch Model to obtained item fit (validity), reliability, distinction level, and difficulty level. The results show that 19 of the 21 questions of SPS instrument have item validity and 14 of 15 questions of SCS instrument have item validity. Besides that, the item reliability of the SPS and SCS test instrument is 0.79 and 0.91, respectively. Meanwhile, the person reliability is 0.82 (SPS) and 0.91 (SCS). Therefore, the SP-CS test is valid and reliable so that it can be used to measure scientific process skills and scientific creative skills of students in further research.AbstrakAsesmen kreativitas banyak dilakukan dalam bidang yang umum, sedangkan asesmen kreativitas pada bidang yang spesifik masih jarang dilakukan. Penelitian ini bertujuan mengembangkan tes scientific creativity skills yang diintegrasikan dengan tes scientific process skills (SP-CS test) pada konsep gelombang cahaya. Penelitian ini menggunakan prosedur ADDIE. Prosedur penelitian terdiri dari lima tahap yaitu menganalisis, merancang, mengembangkan, mengimplementasikan, dan mengevaluasi. Draf awal tes SP-CS terdiri dari 21 soal pilihan ganda scientific process skills (SPS) dan 15 soal uraian scientific creative skills (SCS). Hasil penilaian ahli dianalisis menggunakan indeks validitas isi (CVI), diperoleh nilai 0,75 (sangat sesuai) untuk instrumen SPS dan 0,60 (sesuai) untuk instrumen SCS. Setelah direvisi berdasarkan saran ahli, instrumen tes diujicobakan pada 33 siswa (20 perempuan, 13 laki-laki) berusia 17-18 tahun. Hasil uji coba dianalisis menggunakan Model Rasch untuk memperoleh kecocokan butir (validitas), reliabilitas, daya pembeda, dan tingkat kesukaran. Hasil penelitian menunjukkan bahwa 19 dari 21 butir instrumen tes SPS dan 14 dari 15 butir instrumen tes SCS memiliki validitas item. Selain itu, reliabilitas butir soal instrumen tes SPS dan SCS berturut-turut adalah 0,79 dan 0,91. Sedangkan, reliabilitas responden sebesar 0,82 (SPS) dan 0,91 (SCS). Oleh karena itu, tes SP-CS ini valid dan reliabel sehingga dapat digunakan untuk mengukur keterampilan proses ilmiah dan keterampilan kreatif ilmiah siswa dalam penelitian selanjutnya.How To Cite: Athiyyah, R., Feranie, S., Ramalis, T.R. (2022). Development of Scientific Process-Creative Skills (SP-CS) Test on Light Wave Concept: Rasch Model Analysis. EDUSAINS, 14 (2) : 111-125